Studi Kebutuhan Pengembangan SDM Pengajar Bahasa Mandarin untuk Mendukung Ekonomi Kreatif dan Pariwisata - Romy, Elly; Lisa, Mei; -, Wenny; -, Ivana; Hualangi, Cynthia (JEBIM Prima, 2025)
This study highlights the misalignment between the competencies of Mandarin language instructors and the demands of the creative economy and tourism sectors in Indonesia. The main objective is to identify the developmental needs of human resources in Mandarin instruction and to formulate a training model relevant to industry requirements. The method used is a library research approach with descriptive-qualitative analysis, utilizing sources such as books, academic journals, and research reports. Data were analyzed using content analysis techniques to examine the required competencies in the field. The findings reveal that the integration of linguistic proficiency, intercultural communication, and technological teaching skills is an urgent need that is currently not well accommodated in existing training programs.